2011
DOI: 10.1111/j.1600-065x.2011.01082.x
|View full text |Cite
|
Sign up to set email alerts
|

α‐Defensins in human innate immunity

Abstract: Defensins are small, multifunctional cationic peptides. They typically contain six conserved cysteines whose three intramolecular disulfides stabilize a largely β-sheet structure. This review of human α-defensins begins by describing their evolution, including their likely relationship to the Big Defensins of invertebrates, and their kinship to the β-defensin peptides of many if not all vertebrates, and the θ-defensins found in certain non-human primates. We provide a short history of the search for leukocyte-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
384
1
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 374 publications
(398 citation statements)
references
References 373 publications
(496 reference statements)
5
384
1
8
Order By: Relevance
“…Moreover, MeGlu 21 -HD5 activity was comparable with HD5 activity against E. coli, indicating that E. coli killing is independent of defensin dimerization. We and others have shown that a number of Gram-negative bacterial strains can be killed effectively independent of ␣-defensin structure and chirality (1). The present study further underscores the mechanistic difference in the bactericidal activity of ␣-defensins against these two bacterial strains, one mediated by achiral electrostatic attractions, such as to membrane phosphate groups, and the other mediated partially by hydrophobic interactions that result in specific binding to molecules, such as lipid II.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Moreover, MeGlu 21 -HD5 activity was comparable with HD5 activity against E. coli, indicating that E. coli killing is independent of defensin dimerization. We and others have shown that a number of Gram-negative bacterial strains can be killed effectively independent of ␣-defensin structure and chirality (1). The present study further underscores the mechanistic difference in the bactericidal activity of ␣-defensins against these two bacterial strains, one mediated by achiral electrostatic attractions, such as to membrane phosphate groups, and the other mediated partially by hydrophobic interactions that result in specific binding to molecules, such as lipid II.…”
Section: Discussionmentioning
confidence: 65%
“…The molecular basis of the myriad ␣-defensin functions is gradually being elucidated (1). Many of the prior studies have been focused on two model systems: HNP1 and ␣-defensins from mouse crypts, also known as cryptdins (50).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These data support the involvement of CD30 in the negative control of immune responses directed against self-antigens, a setting largely including tumor-specific T cells. In addition to CD30, other genes were upregulated in SNBs from progressing patients: HMGA1, a transcriptional factor regulating the IFN, IL2, and IL4 genes and recently reported to play a role in transcriptional silencing of the CD4/CD8 loci in the T-cell lineage (30); BSG, which encodes the CD4 þ Foxp3 þ Tregactivation marker CD147 (15), here resulting expressed by nodal CD30 þ lymphocytes; and DEFA1, which encodes defensin a, which has been reported to attract immature DCs and sustain chronic inflammation (31). In addition to the upregulation of defined immune-related genes, GSEA demonstrated that SNBs from patients with poor outcomes displayed a prominent pattern of the reduced expression of genes associated with immunologic responses, thus indicating transcriptional downregulation associated with immune-function impairment.…”
Section: Discussionmentioning
confidence: 99%
“…HNP1 belongs to the α-defensin family and is contained within azurophilic granules of neutrophils with other HNPs (HNP 2−4). When these granules fuse with phagosomes, HNPs are thought to be released to pathogen or phagocytic surfaces and cause disruption of microbial membrane to kill bacteria (22).…”
mentioning
confidence: 99%